Evaluating the impact of NCLB school interventions in New York State: Does one size fit all? - Lee, Jaekyung; Shin, Hyejin; Amo, Laura C. (Education Policy Analysis Archives, 2013)
This study examines the efficacy and moderators of New York State interventions for schools in need of improvement under NCLB, including: (1) school transfer, (2) supplementary education service (3) corrective action, (4) planning for restructuring, and (5) restructuring. Despite the fact that schools in increasingly aggressive treatment groups had higher performance gains relative to schools in good standing, propensity score matching analysis results reveal negative or null effects of the interventions. There are indications of treatment effect heterogeneity and the effects varied by the year of implementation and the propensity of treatment assignment (schooling conditions prior to interventions). The findings of our study have implications for both theory of action and program implementation.